2011
DOI: 10.1038/mp.2010.137
|View full text |Cite
|
Sign up to set email alerts
|

APOE E4 status predicts age-related cognitive decline in the ninth decade: longitudinal follow-up of the Lothian Birth Cohort 1921

Abstract: Carriers of the APOE E4 allele have an increased risk of developing Alzheimer's disease. However, it is less clear whether APOE E4 status may also be involved in non-pathological cognitive ageing. The present study investigated the associations between APOE genotypes and cognitive change over 8 years in older community-dwelling individuals. APOE genotype was determined in 501 participants of the Lothian Birth Cohort 1921, whose intelligence had been measured in childhood in the Scottish Mental Survey 1932. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 40 publications
6
119
2
Order By: Relevance
“…If this evidence is accepted, it seems reasonable to assume that APOE4 might produce a series of accumulative deficits on brain functioning leading to an impaired cognitive performance, irrespective of the subsequent development of AD. In fact, some studies reported cognitive deficits in healthy APOE4 carriers at remarkably young ages [7, 55], a greater acceleration of memory decline prior to age 60 [56], and a worse cognitive status in the ninth decade [57]. Overall, results of these investigations represent a strong support for the cognitive phenotype hypothesis and for the notion that APOE4 effects exceed the AD spectrum.…”
Section: Discussionsupporting
confidence: 72%
“…If this evidence is accepted, it seems reasonable to assume that APOE4 might produce a series of accumulative deficits on brain functioning leading to an impaired cognitive performance, irrespective of the subsequent development of AD. In fact, some studies reported cognitive deficits in healthy APOE4 carriers at remarkably young ages [7, 55], a greater acceleration of memory decline prior to age 60 [56], and a worse cognitive status in the ninth decade [57]. Overall, results of these investigations represent a strong support for the cognitive phenotype hypothesis and for the notion that APOE4 effects exceed the AD spectrum.…”
Section: Discussionsupporting
confidence: 72%
“…In line with this pattern, longitudinal studies have documented interactions between age and APOE on the memory and learning subdomains of the Adult Verbal Learning Test, with stronger negative effects of ε4 in persons older than 50 years than in those below 50 years (Liu et al 2010). Similarly, in older adults aged 79 years, the ε4 allele was associated with more rapid decline in verbal memory and abstract reasoning across 8 years (Schiepers et al 2012). Importantly, one study showed that the relationship of APOE to episodic memory and global cognition was attenuated, after exclusion of future dementia cases (Laukka et al 2013).…”
Section: Apoe Polymorphismmentioning
confidence: 66%
“…In line with this pattern, longitudinal studies have documented interactions between age and APOE, with increasing negative effects of e4 in persons older than 50 years on learning and episodic memory ( Figure 2) [22]. In another study, e4 carriers showed exacerbated decline in verbal memory and reasoning between 79 and 87 years of age [23]. So far, most genome-wide association studies (GWAS) with healthy adults have not used cognitive decline as the outcome or stratified the data across age groups.…”
Section: The Resource-modulation Hypothesismentioning
confidence: 67%